Telomerase Reverse Transcriptase Polymorphism rs2736100: A Balancing Act between Cancer and Non-Cancer Disease, a Meta-Analysis - Snetselaar, Reinier; van Oosterhout, Matthijs F. M.; Grutters, Jan C.; van Moorsel, Coline H. M. (Frontiers in Medicine, 2018)
The enzyme telomerase reverse transcriptase (TERT) is essential for telomere maintenance. In replicating cells, maintenance of telomere length is important for the preservation of vital genetic information and prevention of genomic instability. A common genetic variant in TERT, rs2736100 C/A, is associated with both telomere length and multiple diseases. Carriage of the C-allele is associated with longer telomere length, while carriage of the A- allele is associated with shorter telomere length. Furthermore, some diseases have a positive association with the C and some with the A allele. In this study, meta-analyses were performed for two groups of diseases, cancerous diseases, e.g. lung cancer and non-cancerous diseases, e.g. pulmonary fibrosis, using data from genome wide association studies and case-control studies. In the meta-analysis it was found that cancer positively associated with the C allele (pooled OR 1.16 [95%CI 1.09-1.23]) and non-cancerous diseases negatively associate with the C allele (pooled OR 0.81 [95%CI 0.65-0.99]). This observation illustrates that the ambiguous role of telomere maintenance in disease hinges, at least in part, on a single locus in telomerase genes. The dual role of this SNP also emphasizes that therapeutic agents aimed at influencing telomere maintenance should be used with caution.